IPTEKS BAGI GURU DALAM MENERAPKAN PEMBELAJARAN AKTIF - Nindiasari, Hepsi; Fakhrudin, Fakhrudin (Universitas Sultan Ageng Tirtayasa, 2016)
Based on the initial survey of the learning process in the classroom who do teachers in District Kragilan obtained the data that teachers still tend to use an approach teacher centered, so that the activity of students in the classroom tend to be passive. Students just sit quietly, listen and note what is presented by the teacher at the blackboard. Consequently the results obtained by the students learn less than satisfactory. One of the steps that can be taken to change the way teachers teach is to improve the learning process that emphasizes active student. Student centered emphasis will be successful when teachers have been able to apply active learning, with active learning based contextual issues described above will be overcome with good. The teachers are trained create a learning environment that supports active learning, understand the curriculum in 2013, the preparation of high-level questions and designing student worksheets and authentic assessment. So after this training of teachers capable of designing learning, and learning devices in accordance with the demands of active learning and curriculum 2013. After pelatiha activities continued with mentoring activities. Training in two schools turned out to have a positive impact, including experienced teachers directly in applying active learning because of the assistance. The results of the implementation in the classroom, students become positive attitude with good category.